Reporte de un probable caso de Hemoglobina S / Talasemia Beta. - RAMÍREZ CUENTAS, John; LIZAMA OLAYA, Olga; MARTÍNEZ LA ROSA, Josilú; JHONG OLIVERA, Mercy; SALAZAR LINDO, Eduardo (Revista Médica Herediana, 2013)
We report the case of a patient with Hemoglobin S / Thalassemia. It is feasible to recognize this infrequent disease by its clinical presentation and the aid of clinical laboratory . On this patient, the diagnosis was established based on the clinical findings, hematological evaluation (with careful observation of the red cell morphology and reticulocyte count) and electrophoretic analysis of hemoglobin. We discusse the physiopathology, clinical manifestations, treatment and alternative of prevention of this disease.